Intro to the Java module system and migrating code to Java 11. (Manning Publications, 2020)
In his extensive and detailed live coding session, developer, author, speaker, and trainer Nicolai Parlog shows compatibility challenges when moving to Java 11, while explaining how to turn JARs into modules.